Laboratory Medicine in Healthcare - Singh, Gurmukh (Archives of Clinical and Biomedical Research, 2025)
Laboratory medicine provides essential information that drives 70% of clinical decisions. Interpretation of patient results requires comparison with normal values/reference ranges. Normal values vary by age, gender, ethnicity, and testing methods. Finding “healthy” individuals to ascertain normal values is an intractable issue, further complicated by the general practice of using the central 95% of values. Matters are made more difficult by the observation of a paradox between medically prescribed ranges and optimal ranges based on longevity data. Reporting of laboratory results on patient portals may cause unwarranted concern due to minor differences in a patient’s results from “normal” values. Reducing the spread of normal values warrants developing reference ranges specific for age, gender, ethnicity, geographic area and methods of testing. Using minimally necessary levels of essential trace nutrients versus optimal levels is a source of confusion in determining normal values. In addition to reporting the raw results on patient portal a brief interpretation addressing the importance of variation from normal values should be included to avoid unwarranted concerns by patients. Judicious use of laboratory testing is important for not only cost controls but also to avoid incurring additional clinically meaningless variations from normal values due to increased volume of tests.